A snapshot of agricultural research investment and capacity in Asia - Stads, Gert-Jan (Asia-Pacific Association of Agricultural Research Institutions, 2017)
Since the turn of the millennium, Asia has recorded rapid growth in its levels of agricultural research spending. Most of the growth in regional spending was driven by China. Spending in India and Indonesia has also increased substantially since 2000. However, many countries in Asia continue to underinvest in agricultural research. Cambodia, Lao PDR, and Pakistan still invest less than 0.20 per cent of their agricultural GDP in agricultural research, which is clearly insufficient considering the numerous emerging challenges these countries face, including widespread poverty, rapid population growth, climate change, and environmental degradation. On a positive note, the number of Ph.D. qualified agricultural researchers has risen in nearly all Asian countries since 2000, although in some countries–particularly Nepal, Pakistan, and Vietnam–many senior researchers are approaching retirement age. Women remain severely underrepresented in agricultural research in Asia. Many countries have a long way to go to ensure that female perspectives are integrated within research agendas.